Anti-inflammatory activity of curcumin-loaded tetrahedral framework nucleic acids on acute gouty arthritis - Zhang, Mei; Zhang, Xiaolin; Tian, Taoran; Zhang, Qi; Wen, Yuting; Zhu, Junyao; Xiao, Dexuan; Cui, Weitong; Lin, Yunfeng (Bioactive materials, 2022)
Gouty arthritis is a very familiar inflammatory arthritis. Controlling inflammation is the key to preventing gouty arthritis. However, colchicine, the most highly represented drug used in clinical practice, has strict contraindications owing to some severe side effects. Curcumin (Cur), a natural anti-inflammatory drug, has demonstrated good safety and efficacy. However, the rapid degradation, poor aqueous solubility, and low bioavailability of Cur limit its therapeutic effect. To strengthen the effectiveness and bioavailability of Cur. Cur loaded tetrahedral framework nucleic acids (Cur-TFNAs) were synthesized to deliver Cur. Compared with free Cur, Cur-TFNAs exhibit a preferable drug stability, good biocompatibility (CCK-8 assay), ease of uptake (immunofluorescence), and higher tissue utilization (in vivo biodistribution). Most importantly, Cur-TFNAs present better anti-inflammatory effect than free Cur both in vivo and in vitro experiments through the determination of inflammation-related cytokines expression. Therefore, we believe that Cur-TFNAs have great prospects for the prevention of gout and similar inflammatory diseases. Schematic illustration of treating acute gouty arthritis with Cur loaded TFNAs. Cur-TFNAs were absorbed by inflammatory RAW264.7 cells and inhibited the activation of NF-κB, which decreased the levels of ROS, NO and inflammatory factors (IL-6, IL-1β and TNF-α), thus affecting the progression of acute gouty arthritis. [Display omitted] •The drug curcumin system based on DNA nanostructures (Cur-TFNAs) were developed to obtain a novel nanomaterial with high water solubility, large encapsulation efficiency, sustained drug release and excellent drug stability.•Based on cellular uptake and in vivo drug imaging, Cur-TFNAs improve the retention of Cur in cells and tissues.•Cur-TFNAs prevent acute gouty arthritis through mediating anti-inflammatory and antioxidant responses of macrophage.